Malaria Hepatopathy and Thrombocytopenia in Severe Falciparum Malaria - Arfijanto, Muhammad Vitanata; Wahyudi, Mohammad Imam (The Indonesian Society for Digestive Endoscopy, 2023)
Jaundice commonly occurs in severe malaria, seen in approximately 2,5% patients with falciparum malaria infection. Jaundice in malaria can be caused by intravascular hemolysis, disseminated intravascular coagulation (DIC) or malaria-related liver disorders. Malaria hepatopathy is a term that is often used to describe hepatocytic dysfunction in severe malaria, although inflammation does not occur in the liver parenchyma. Malaria hepatopathy also characterized by a rise in serum bilirubin along with the rise in serum glutamate pyruvate trasnaminase levels. This two condition are similar but must be distinguished because of different treatment required.